The Caucasus Clergy in the Policy of Tsarist Russia - Gürer, Banu; Tağıyeva, İrade (Scholarya Demo Journal of Ruby, 2019)
This research, focusing on the religious policy of Tsarist Russia, presents the differences between Shiite and Sunni religious organizations based on their own original regulations along with general information about the institutions governing religious affairs and these two religious administrations. With regard to the purpose of the research, the issues of religion and education in Russian state structure were studied and a background was formed for the understanding of the religious structure before touching upon the issue of religious institutions. Tsarist period was evaluated in terms of Islamic policy and from the occupation of Caucasus to the revolution of 1917, it was determined that two different approaches, both moderate and intolerant, emerged in politics in the last part of the research. Despite some developments in the field of education in the moderate policy process, Muslims’ demand for the unification of religious administrations under one roof had not yielded the expected results. This demand was fulfilled only with the establishment of “Mashihat” administration during ADR (Azerbaijan Democratic Republic) period.